Building a bridge between science and practice in sport swimming: from black box to multi-factorial models - Kolmogorov, S.; Vorontsov, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Modern training of elite swimmers makes a steady and rapid transition from training based on a «black box» model: «input (parameters of physical workload) - output (training or racing results) » to training which requires a regular evaluation and monitoring of physical and technical preparedness parameters of athletes. Apparently, this approach demands close cooperation and understanding between sports coaches and scientific support staff. Such cooperation results in better knowledge among sports coaches about internal mechanisms of adaptation and functioning of metabolic and biomechanical systems. Knowledge of the functional relationship between metabolic abilities and biomechanical characteristics on the one hand and useful result of motor activity (swimming velocity) on the other been formalized in the form of several biophysical models (Di Prampero et al., 1974; Toussaint & Beek, 1992; Ribeiro et al., 2017; Zamparo, Cortesi, & Gatta, 2020; Kolmogorov et al., 2021). These biophysical models allow using a more efficient multi-factorial approach to the planning of training and monitoring of its efficiency. Thus, the aim of the study was to improve the efficiency of training swimmers for medium distances based on a regular and interconnected analysis of the main biophysical fitness criteria.